1985
DOI: 10.1002/star.19850370804
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Starch Obtained from Potato Tubers Influenced by Various Temperatures

Abstract: The properties of starch separated from potato tubers were studied regarding the following storage temperatures: +20 °C, +8 °C, +4 °C and 0 °C. The study included also potato tubers having been frozen, thawed and refrozen as well as potato tubers before storage. Starch separated from the stored potato tubers showed differences in chemical composition, reducing power, granularity, whiteness and viscosity as well as gelatinization temperatures in comparison with the starch separated from potato tubers before sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
(7 reference statements)
1
12
2
Order By: Relevance
“…There are confl icting reports about the effect of storage on the viscosity of starch. Golachowski (1985) reported an increase in viscosity of starch separated from potatoes stored for 12 weeks at 8 and 12°C whereas, Ridley and Hogan (1976) observed a decrease in viscosity of starch separated from potatoes stored for 3 months at 1.7 and 7.2°C. P, K and Ca contents of starch are also affected by storage conditions (Mica 1976).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…There are confl icting reports about the effect of storage on the viscosity of starch. Golachowski (1985) reported an increase in viscosity of starch separated from potatoes stored for 12 weeks at 8 and 12°C whereas, Ridley and Hogan (1976) observed a decrease in viscosity of starch separated from potatoes stored for 3 months at 1.7 and 7.2°C. P, K and Ca contents of starch are also affected by storage conditions (Mica 1976).…”
Section: Introductionmentioning
confidence: 85%
“…Storage temperature affects not only the quantity but also the quality of potato starch (Leszczynski 1989). Jhonston et al (1968) observed an increase in amylose content after storage while Golachowski (1985) reported a decrease. There are confl icting reports about the effect of storage on the viscosity of starch.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The structures and physical properties vary with botanical origin, growing conditions, mutations, and maturity (Boyer et al 1976, Golachowski 1985, Swinkels 1985, Asaoka et al 1985, Kolodzie] 1993). Starch consists of two major forms of polysaccharides;…”
Section: Literature Review General Properties Of Starchmentioning
confidence: 99%
“…Starch granule size and shape vary with botanical origin {such as potato-starch granules are oval shaped (15-80 //m), normal-maize starch-granules are round or polygonal shaped (5-20 //m), and tapioca-starch granules are round shaped (3-18 /wm)}, maturity, and growing condition (Banks et al 1974, Greenwood 1979, Golachowski 1985, iVlorrison and Gadan 1987. Scanning electron microscopy (SEM) has been used to study the morphology and surface of starch granules.…”
Section: Starch Granulesmentioning
confidence: 99%